SIKAP-SIKAP POSITIF MAHASISWA YANG BERTUMBUH PESAT SEJAK DUDUK DI BANGKU KULIAH - Sudarto, Sudarto (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This research is a survey research that aims to find out what positive attitudes have been embedded or growing rapidly in the students as prospective teachers since attending in ihe college. The research subjects were 20 students of the Elementary School Teacher Education (ESTE) study program, FIP UNM, the Sixth Campus of Bone. The research instruments used in this study were questionnaires and interview sheets. Questionnaire sheets and interview sheets were used to collect data about the positive attitudes of students that had developed since they were in college. The data analysis technique used is content and percentage analysis. The results of the study show that there are 12 positive attitudes that have grown rapidly in students since they were in college, namely: friendly attitude (in 100% of students), polite and independent attitude (in each of 95% of students), diligent and forgiving attitude (90% of students each), discipline, patience, collaboration, and confidence (85% of students each), wise and honest (80% of students each), and critical attitude (75% of students) student). Conclusion: Positive attitudes that have grown rapidly in the students since they were in college were: friendly, polite, independent, diligent, forgiving, disciplined, patient, collaborative, confident, wise, honest, and critical